The Effect of COVID-19, Commodity Prices, and Exchange Rate on Indonesian Stock Market - Almira Intan Nurrahma (Jurnal Keuangan dan Perbankan, 2022)
The purpose of this study is to examine the impact of COVID-19, exchange rate, and commodity prices on the performance of stock markets, focusing on the Arbitrage Pricing Theory (APT) and behavioral influence of the sentiment due to COVID-19. To accomplish this, search volumes compiled by Google Trends on the topic of COVID-19 were used as a proxy for COVID-19 sentiment. The results from applying a panel data approach, using a data set of 35 stocks listed LQ45 index, for the period January 1, 2020, to December 31, 2021, showed that COVID-19 cases and exchange rate have a negative effect on the stock markets. Conversely, commodity prices positively affect the stock markets. However, the estimation fails to reflect the significant impact of the COVID-19 sentiment on stock markets, but it has a positive effect on stock markets. This result implies that (1) higher COVID-19 cases are still a source of weakness in the Indonesian stock market, (2) Positive sentiment suggests that Indonesian investors are more optimistic throughout the pandemic period.